Comparison of Clinical Outcomes Between Acetylcysteine and Ambroxol in Post Acute Exacerbation of COPD Patients - Molidia, Sri Rahmat; Pramantara, Dewa Putu; Ikawati, Zullies (Fakultas Farmasi Universitas Andalas, 2024)
Literature studies show that the use of acetylcysteine or ambroxol can accelerate improvement of clinical outcomes of post acute exacerbation chronic obstructive pulmonary disease (AECOPD) patients. This study aims to compare the clinical outcomes of acetylcysteine and ambroxol administration in post AECOPD patients. The study was cohort design, prospective, to comparison of clinical outcomes of acetylcysteine and ambroxol with post AECOPD outpatients coming for clinical chekups in August 2023 at Respira Lung Hospital Yogyakarta. Clinical outcomes parameters were observed on day zero and thirty for CAT score and day zero and four for cough score. The patients were categorized into two groups: acetylcysteine group (n=30) and ambroxol group (n=30). There was no significant difference between two groups to change of CAT score and cough score (p>0.05) post AECOPD. The acetylcysteine group compared to ambroxol, there was a mean decrease in morning cough score -1.10±1.11 vs -0.87±1.12 (p=0.228), night cough score -1.53±1.43 vs -1.13±1.31 (p=0.438), and CAT score -2.43±5.45 vs -2.90±3.41 (p=0.391). Providing additional therapy of acetylcysteine or ambroxol in this study did not significantly reduce cough scores and CAT scores in post AECOPD patients.